Progress in quality control, detection techniques, speciation and risk assessment of heavy metals in marine traditional Chinese medicine - Yuan-sheng Guo; Tian-tian Zuo; An-zhen Chen; Zhao Wang; Hong-yu Jin; Feng Wei; Ping Li; Shuang-cheng Ma (BMC, 2023)
Abstract Marine traditional Chinese medicines (MTCMs) hold a significant place in the rich cultural heritage in China. It plays an irreplaceable role in addressing human diseases and serves as a crucial pillar for the development of China's marine economy. However, the rapid pace of industrialization has raised concerns about the safety of MTCM, particularly in relation to heavy metal pollution. Heavy metal pollution poses a significant threat to the development of MTCM and human health, necessitating the need for detection analysis and risk assessment of heavy metals in MTCM. In this paper, the current research status, pollution situation, detection and analysis technology, removal technology and risk assessment of heavy metals in MTCM are discussed, and the establishment of a pollution detection database and a comprehensive quality and safety supervision system for MTCM is proposed. These measures aim to enhance understanding of heavy metals and harmful elements in MTCM. It is expected to provide a valuable reference for the control of heavy metals and harmful elements in MTCM, as well as the sustainable development and application of MTCM.